An Empirical Analysis of Rentability and Macroeconomics Affecting Liquidity on Indonesian Islamic Bank - Amru Aziz Shobbarin (International Conference on Industrial Revolution for Polytechnic Education, 2019)
This study aims to empirically examine the effect of rentability and macroeconomics on the liquidity of Islamic banking in Indonesia. In this study rentability is proxied by Operating Expenses to Operations Revenue (OEOR), Return on Asset (ROA), and Return on Equity (ROE). Macroeconomics is proxied by Gross Domestic Product (GDP), Inflation Rate (INF), and Central Bank Rate (CBR), and then Financing to Deposit Ratio (FDR) as a proxy for liquidity. This study uses multiple linear regression or least square analysis techniques using data from the fourth quarter of 2008 to the second quarter of 2018 sourced from Indonesian Central Bank (BI – Bank Indonesia), Financial Service Authority (OJK – Otoritas Jasa Keuangan), and Central Statistics Agency (BPS – Badan Pusat Statistik). The results of this study found that OEOR and CBR had a significant effect on FDR. But, ROA, ROE, GDP and INF have no effect on FDR. These results indicate that profitability and macroeconomics both affect the liquidity of Islamic banking in Indonesia.